Late gadolinium enhancement as a predictor of arrhythmias in patients with hypertrophic cardiomyopathy. (24th May 2021) - Castelo, A; Rosa, S; Fiarresga, A; Marques, M; Portugal, G; Cunha, P; Bras, P; Ferreira, V; Mendonca, T; Oliveira, M; Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients with hypertrophic cardiomyopathy (HCM) are at increased risk of arrhythmias and sudden cardiac death (SCD). The Late gadolinium enhancement (LGE) in cardiovascular magnetic resonance (CMR) has been associated with the occurrence of arrhythmic events. Purpose: The aim was to analyze the association between LGE burden and location and arrhythmic events in HCM patients (P). Methods: Retrospective analysis of P with HCM in a single tertiary center. Baseline clinical, echocardiographic and CMR characteristics were collected. On follow up arrhythmias (ventricular fibrillation (VF), sustained ventricular tachycardia (SVT), non-sustained ventricular tachycardia (NSVT), paroxysmal supraventricular tachycardia (PSVT), atrial fibrillation (AF) and atrial flutter (AFL)) were identified. LGE on CMR was compared between patients with and without arrhythmias. Results: 61P (59% male) were included, with a mean age of 58 ± 2 years. The HCM risk-SCD score was 3.35 ± 0.28%. On echocardiography mean left ventricle ejection fraction was 62.16 ± 1.36% and maximum wall thickness 20.59 ± 0.596mm. 31.1% had systolic anterior movement of mitral valve and 26.7% had left ventricle outflow tract obstruction. LGE was present in 88.5% P with a median number of 5 ± 7 segments involved. Interventricular septum (IVS) was involved in 78.7% P, anterior wall in 57.4%, inferior wall in 54.1%, lateral wall in 52.5%, posterior wall in 9.8%, basal segments in 62.3%, median segments in 68.9% and apical segments in 63.9%. On follow up 3.3%P died, 45.8% had hospitalizations (22, 2% because of an arrhythmia) and 75% had arrhythmias (1.6% VF, 6.6% SVT, 50% NSVT, 9.8% PSVT, 37.7% AF and 6.6% AFL). The number of segments with LGE correlated with arrhythmias (p = 0.05 for arrhythmias, p = 0.03 for SVT, p = 0.008 for NSVT and p = 0.042 for PSVT). A cut off of 5 segments involved was a good predictor of arrhythmias (p = 0.002), NSVT (p= 0.006), PSVT (p = 0.024) and AF (p = 0.0029). For SVT the best cut off was 9 (p = 0.003). Considering the LGE location, we found an association between the segments involved and the occurrence of different arrhythmias (table 1). Conclusion: Supraventricular and ventricular Arrhythmias are frequent in patients with HCM, with the most frequents being NSVT and AF. The LGE burden (>5 segments) and location (median inferior IVS, median anterior IVS, median anterior wall, basal anterior IVS, apical anterior wall, median inferior wall, apical anterior wall and basal inferior IVS) were correlated with arrhythmic events.